Table of contents, editorial board, and other front matter - James P. Chapman (Journal of Applied Communications, 1976)
Editorial front matter and table of contents for vol. 59, no. 1, Jan.-Mar. (1976) of ACE, the official journal of the American Association of Agricultural College Editors.